Population dynamics and spatial dist'ribution of tlle terrestrial snail Ovachlamys fulgens (Stylommatopbora: Helicarionidae) in a tropical environment - Barrientos, Zaidett (Revista de Biología Tropical, 2000)
The introduced snail Ovachlamys fulgens (Stylommatophora: Heliearionidae) oeeurs on cultivated land habitats in Costa Rica, where its macrodistribution seems to be limited by annual mean temperature (20 - 27.6°C) and annual preeipitation (1 530 - 3 034 and 3 420 - 8 000 mm, with no more than s ix dry months). This species can be found in ¡itter and on vegetation up to 70 cm tal\. Random quadrat field sampling was done in leaf l itter and understory plants every three months for a total of five dates in Central Costa Rica. At least 1 50 plots of 2Sx25 cm were analyzed on each date. Abundance of living specimens and eggs was positively correlated with ( 1 ) litter abundance and depth, (2) litter and soil humidity, (3) relative humidity and (4) early moming temperature (6:30 AM), and negatively correlated w ith temperature later in the moming ( 1 0:00 AM). Besides these factors, living snail abundance was eorrelated with thickness of the herbaeeous vegetation and with the oeeurrence of fueca elephantiphes (in litter and understory). Egg abundanee was also correlated with the sampling date, apparently because of changes in humídity. The correlation pattem of shell abundance was opposite to that of living specimens. Population size and number of empty shells throughout the year parallel the rainfall pattem. Reproduetion takes place between May and November (wet season); and up to 92% of the specimens can be found aestivating between December and April (dry season). Clutch s ize averages three eggs. The maximum density of living specimens was reaehed in D ecember (43.4 1 ind/m2) and the mínimum in March (8.30 ind/m2) . Shells decompose in all average of five months.